Does maritime Antarctic permafrost harbor environmental fungi with pathogenic potential?. Issue 8 (August 2022) - da Silva, Thamar Holanda; Queres Gomes, Eldon Carlos; Gonçalves, Vívian Nicolau; da Costa, Marliete Carvalho; Valério, Aline Dias; de Assis Santos, Daniel; Johann, Susana; Convey, Peter; Rosa, Carlos Augusto; Rosa, Luiz Henrique
Abstract: We assessed the potentially pathogenic fungi present in Antarctic permafrost and the overlying active layer on King George, Robert, Livingston and Deception Islands in the South Shetland Islands archipelago, maritime Antarctica. Permafrost and active layer sub-samples were incubated at 37 °C to select fungi able to grow inside the human body. A total of 67 fungal isolates were obtained, 27 from the permafrost and 40 from the active layer. These represented 18 taxa of the genera Alternaria, Aspergillus, Curvularia, Penicillium, Rhodotorula and Talaromyces . The majority of fungi detected occurred exclusively either in the permafrost or the active layer at each site. Only Aspergillus thermomutatus, Penicillium cf. chrysogenum and Rhodotorula cf. mucilaginosa were present in both permafrost and active layer samples from the same site. The yeast R. cf. mucilaginosa was recovered from both in at least two sites. The genus Penicillium was the most abundant and widely distributed genus in both permafrost and active layer samples across the sites sampled. All fungal isolates were screened using enzymatic, pH and antifungal assays to identify their virulence potential. Aspergillus hiratsukae, A. thermomutatus and R. cf. mucilaginosa, known human opportunistic fungi, were identified, displayed phospholipase, esterase, proteinase and hemolytic activities. All three also displayed the ability to grow at 40°, 45° and/or 50 °C and resistance to fluconazole and itraconazole; additionally, R. cf. mucilaginosa showed resistance to amphotericin B and viability after 100 d at −80 °C. A. thermomutatus UFMGCB 17415 killed the entire larvae of Tenebrio molitor in six days and R. cf. mucilaginosa UFMGCB 17448 and 17473 in three and four days, respectively. The melting of maritime Antarctic permafrost as a result of climate change may threaten the release of wild strains of pathogenic fungi geographically isolated for long time, which may in turn be transported within and beyond Antarctica by different biological and non-biological vectors. Graphical abstract: Image 1 Highlights: We assessed the potentially pathogenic fungi in Antarctic permafrost. Taxa of Alternaria, Aspergillus, Curvularia, Penicillium, Rhodotorula and Talaromyces were identified. Aspergillus and Rhodotorula species displayed resistance to fluconazole and itraconazole. Aspergillus thermomutatus and Rhodotorula cf. mucilaginosa kill the entire larvae of Tenebrio molitor .